A decade of aid coordination in post-conflict Burundi’s health sector - Cailhol, Johann (Global Health, 2019)
BACKGROUND: The launch of Global Health Initiatives in early 2000′ coincided with the end of the war in Burundi. The first large amount of funding the country received was ear-marked for human immunodeficiency virus (HIV) and immunization programs. Thereafter, when at global level aid effectiveness increasingly gained attention, coordination mechanisms started to be implemented at national level. METHODS: This in-depth case study provides a description of stakeholders at national level, operating in the health sector from early 2000′ onwards, and an analysis of coordination mechanisms and stakeholders perception of these mechanisms. The study was qualitative in nature, with data consisting of interviews conducted at national level in 2009, combined with document analysis over a 10 year-period. RESULTS: One main finding was that HIV epidemic awareness at global level shaped the very core of the governance in Burundi, with the establishment of two separate HIV and health sectors. This led to complex, nay impossible, inter-institutional relationships, hampering aid coordination. The stakeholder analysis showed that the meanings given to ‘coordination’ differed from one stakeholder to another. Coordination was strongly related to a centralization of power into the Ministry of Health’s hands, and all stakeholders feared that they may experience a loss of power vis-à-vis others within the development field, in terms of access to resources. All actors agreed that the lack of coordination was partly related to the lack of leadership and vision on the part of the Ministry of Health. That being said, the Ministry of Health itself also did not consider itself as a suitable coordinator. CONCLUSIONS: During the post-conflict period in Burundi, the Ministry of Health was unable to take a central role in coordination. It was caught between the increasing involvement of donors in the policy making process in a so-called fragile state, the mistrust towards it from internal and external stakeholders, and the global pressure on Paris Declaration implementation, and this fundamentally undermined coordination in the health sector. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12992-019-0464-z) contains supplementary material, which is available to authorized users.